Synergizing early detection and comprehensive mandatory notification to improve Tuberculosis case finding through public private mix - Artawan Eka Putra, I Wayan Gede (Public Health and Preventive Medicine Archive, 2022)
Tuberculosis (TB) is a priority health problem in Indonesia. Incidence rate estimation for TB in 2020 was 301 per 100,000 population or 824,000 new cases per year which is the third highest worldwide. The Corona Virus Disease (COVID-19) Pandemic has caused decreasing performance of TB control program globally, including Indonesia. The treatment coverage was declined from 67% in 2019 to 48% in 2020 and 54% in 2021, far behind the 80% target. This fact signifies that around a half of people with TB in Indonesia are overlooked, which is estimated to be accounted for over 400,000 cases. Another TB Program’s main indicator, treatment success rate at 86%, remains below the target of 90%. Low achievement of the two main indicators may result in the increasing of TB transmission, morbidity and mortality in population. Besides, Indonesia also faces the triple burden of TB, high prevalence of drug resistance TB and coinfection of TB and HIV